2021
DOI: 10.1101/2021.03.01.433344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitroscreening of herbal medicinal products for their supportive curing potential in the context of SARS-CoV-2

Abstract: Background: Herbal medicinal products have a long-standing history of use in the therapy of common respiratory infections. In the COVID-19 pandemic, they may have the potential for symptom relief in non-severe or moderate disease cases. Here we describe the results derived by in vitro screening of five herbal medicinal products with regard to their potential to i) interfere with the binding of the human Angiotensin-converting enzyme 2 (ACE2) receptor with the SARS-CoV-2 Spike S1 protein, ii) modulate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The authors confirm that the first version of this article was uploaded on the preprint server “BioRxiv” before submission [ 49 ]. In vitro screening of herbal medicinal products for their supportive curing potential in the context of SARS-CoV-2 | BioRxiv.…”
Section: Disclosurementioning
confidence: 86%
“…The authors confirm that the first version of this article was uploaded on the preprint server “BioRxiv” before submission [ 49 ]. In vitro screening of herbal medicinal products for their supportive curing potential in the context of SARS-CoV-2 | BioRxiv.…”
Section: Disclosurementioning
confidence: 86%
“…Both trials showed a significantly faster reduction of coughing fits in comparison to placebo, as well as a faster regression of bronchitis-related symptoms and higher responder rates with the herbal product [95,96]. In addition to anti-inflammatory and anti-viral [118] effects, the thyme-ivy/thyme-primula combinations also showed mucus-regulatory effects in acute and chronic bronchitis and bronchoalveolitis [119][120][121].…”
Section: Introductionmentioning
confidence: 96%